A simple template for pitching research. (7th April 2015) - Faff, Robert W.; Smith, Tom
Abstract In this article, I propose a simple new research tool – a template designed for pitching research. The two‐page pitching template begins with four 'preliminaries': working title, research question, key papers and motivation. Following this is the core of the template based on a '3‐2‐1 countdown', namely THREE elements – idea, data and tools; TWO questions – What's new? and So what?; and ONE bottom line – contribution. The template ends with 'other' considerations. Finance and accounting examples are given to illustrate application of the template.